Creative Leadership Signposts in Higher Education - Peterson, Fiona J. author. aut Link
Approx. 250 p.
Keywords: "Creative ways of thinking about leadership are helpful to guide practice and personal growth. This book builds a strategic roadmap for creative leadership practice, putting the spotlight on a leader’s professional development journey in the process. The book is about leadership on the ground in higher education, where the ‘rubber hits the road’. It can also be useful in business, or for anyone wanting to think outside the square. Through a creative storytelling approach, the author takes the reader through Tuscany and her on-the-job experience as a leader of learning and teaching. Along the way, she explains some of the theoretical influences on her thinking and practice – in ways and combinations she hadn’t read about in other leadership books, or experienced in professional development programmes. Through real stories, the author shows how she made creative connections in building her own knowledge on present and past experience, with reflection on how practice can be improved with a clear focus on collegiality and strategic outcomes. This approach reflects the five creative leadership signposts that she explains and illustrates throughout the book. ".